The prevalence of ocular structural disorders and nystagmus among preschool-aged children - Repka, Michael X. (2012)
PURPOSE: To describe the prevalence of structural disorders of the eye and nystagmus in preschool-aged children. METHODS: Population-based evaluation of children 6 months through 71 months of age in Baltimore, Maryland, United States. RESULTS: Among 4,132 children identified from 54 census tracts, 3,990 eligible children (97%) were enrolled and 2,546 children (62%) were examined. Structural disorders were found in 41 children and nystagmus in 9 children for an overall prevalence of 1.96% (95% CI, 1.46%–2.59%). Only 11 (0.43%; 95% CI, 0.22%–0.77%) had vision loss in at least one eye, most often due to posterior segment disease. CONCLUSIONS: Structural ocular abnormalities and nystagmus combined are present in nearly two percent of preschool-aged children in this population-based study. Vision loss due to these abnormalities is uncommon.